The Relationship Between Firm Size and Profitability : “Evidence from the Commercial Banks in Iraq” - Ahmed, Amanj Mohamed (The Scientific Journal of Cihan University– Sulaimaniya, 2022)
This research is aimed to identify the impact of firm size on the profitability of commercial banks. To achieve this goal, a model was developed to measure the relationship between the dependent and independent variables based on the use of simple linear regression method. The secondary data was collected from the audited financial statements of the commercial banks listed on Iraqi stock exchange (ISX) between the years (2011-2014) and statistically analyzed. The dependent variable is (profitability) and measured by the rate of return on assets (ROA) and the independent variable is (firm size) and computed by the indicators of (natural logarithm of total sales (TS), natural logarithm of total assets (TA) and the number of employees (EMP). The results revealed that there is a positive and significant relationship between total assets, number of employees and return on assets. In contrast, a negative association noted between total sales and return on assets. Lastly, the study proposed that future studies should focus on investigating and comparing the impact of applying different sectors to find the relationship between firm size and profitability.